Diffusion of Practice: The Curious Case of the Sino-German Technical Standardisation Partnership. Issue 6 (2nd November 2022) - Fuchs, Daniel; Eaton, Sarah
ABSTRACT: At a time of deepening divisions between China and Global North countries, Germany and China are swimming against the tide by cooperating closely in the highly sensitive area of high-tech standardisation. Based on interviews with participants and close observers of this partnership, we argue that a diffusion of practice logic underpins China's partnership with Germany. Despite the competitiveness of China's high-tech sectors, this latecomer faces both formal and informal barriers to entry in global standardisation processes. By partnering with Germany, one of the globe's leading standards powers, China hopes to both cultivate a powerful ally in an increasingly contentious arena and master the subtleties of standardisation practice by working closely with an insider. For their part, German participants view the diffusion of standardisation know-how as consistent with their interests as a status quo standards power and vital to supporting German industry in China.